Introduction to electronic warfare modeling and simulation - Adamy, David L. (SciTech Publishing, 2006)
This book covers the field of electronic warfare (EW) modeling and simulation at a systems level, including chapters that describe basic EW concepts. Written by well-known expert with more th 40 years of experience in the field, the book explores EW applications and techniques and the radio frequency spectrum, with primary emphasis on high frequency (HF) to microwave. The book offers an in-depth understanding of the basic concepts required for modelling and simulation, as well as fidelity and other practical aspects of simulation design and application. All of the math used in the text, including dB formulas and spherical trigonometry, is fully explained. This informative reference explains the facilitation and generation of realistic computer models of EW equipment are described, as well as how they work and how each is mathematically modeled. Also included is a description of the various types of models, simulations, with applications to training and equipment-testing tasks.